2021
DOI: 10.3389/fendo.2021.765415
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Fat Mass Index and Fat Free Mass Index With Body Mass Index and Association With Function, Cognition and Sarcopenia in Pre-Frail Older Adults

Abstract: BackgroundBody mass index (BMI) is an inadequate marker of obesity, and cannot distinguish between fat mass, fat free mass and distribution of adipose tissue. The purpose of this study was twofold. First, to assess cross-sectional relationship of BMI with fat mass index (FMI), fat free mass index (FFMI) and ratio of fat mass to fat free mass (FM/FFM). Second, to study the association of FMI, FFMI and FM/FFM with physical function including sarcopenia, and cognition in pre-frail older adults.MethodsCross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 69 publications
(84 reference statements)
1
30
0
Order By: Relevance
“…This parameter does not distinguish between FFM and FM nor assesses the amount and distribution of body fat. For these reasons, BMI may lead to a false classification of subjects with normal body mass and excessive fatness as healthy individuals [ 59 , 60 , 61 ]. Some authors demonstrated that fat tissue percentage increased in older subjects independently of body mass.…”
Section: Discussionmentioning
confidence: 99%
“…This parameter does not distinguish between FFM and FM nor assesses the amount and distribution of body fat. For these reasons, BMI may lead to a false classification of subjects with normal body mass and excessive fatness as healthy individuals [ 59 , 60 , 61 ]. Some authors demonstrated that fat tissue percentage increased in older subjects independently of body mass.…”
Section: Discussionmentioning
confidence: 99%
“…BMI also has been used for assessing metabolic disease. However, metabolically health and abnormal obesity can not be distinguished, because the FMI and FFMI can not be distinguished by BMI [34]. Merchant et al reported that FMI was associated with higher rate of sarcopenia, and there was a possibility that the FFMI and FMI were more useful for predicting functional outcome in prefrail patients than BMI [34].…”
Section: Discussionmentioning
confidence: 99%
“…Lower PhA values indicate an increase in the extra water and a decrease in muscle mass [38,39]. PhA has also been associated with osteoarthritis severity [40], functional ability [23,34,41,42], and Barthel's index [43]. It is reported that PhA was associated with muscle strength [44] and quadriceps strength [40].…”
Section: Discussionmentioning
confidence: 99%
“…Propensity score (PS) matching was used for adjusting covariates in both groups [ 21 ]. Previous studies have reported covariate relationships between phase angle and age, height, and FFMI [ 22 , 23 ]. However, some researchers have stated that BMI is a determinant of phase angle [ 13 , 24 ].…”
Section: Methodsmentioning
confidence: 99%